Lesson Study as an Effort to Improve the Quality of Learning In Freedom to Learn - Dina Anika Marhayani; Zulfahita Zulfahita; Andi Mursidi; Abdul Basith; Mariyam Mariyam; Eti Sunarsih; Sumarli Sumarli; Susan Neni Triani; Buyung Buyung; Nindy Citroresmi; Emi Sulistri; Mertika Mertika; Sri Mulyani; Fitri Fitri; Dewi Mariana; Rini Setyowati (STKIP Singkawang, 2022)
The partners of this service activity are teachers throughout West Kalimantan with partner problems, namely a decrease in the quality of learning in Merdeka Learning. Quality learning cannot be separated from the ability of teachers as planners, implementers, facilitators, and evaluators. One of the efforts that can be done to improve the quality of learning is to carry out lesson study. The purpose of this Community Service activity is the formation of a learning community that consistently makes self-improvement in the learning process to reduce the decline in learning outcomes in Merdeka Learning. The method of implementing this activity is mentoring lesson study to teachers throughout West Kalimantan. The implementation follows the method of implementing lesson study, namely planning, implementation, and evaluation. Regarding the usefulness of the activity to the 300 participants, data obtained from 300 people felt that this activity was very useful or equivalent to 100% of the number of participants. This shows that the activity of